Tender the maker: poems - Hutchins, Christina, author; Utah State University Press, publisher (Colorado State University. Libraries, 2015)
Hutchin's poems startle us into awareness of the overlooked, the nearly-always invisible, and the marvelous, those aspects of life that come under the rubric of 'mystery,' in all sense of the word. Hutchins combines a pitch-perfect and precise lyricism with a postmodern sensibility of language's materiality--provided by publisher.
Keywords: American poetry -- 21st century